Functional and Molecular Analysis of Proprioceptive Sensory Neuron Excitability in Mice - Madden, Jessica F.; Davis, Olivia C.; Boyle, Kieran A.; Iredale, Jacqueline A.; Browne, Tyler J.; Callister, Robert J.; Smith, Douglas W.; Jobling, Phillip; Hughes, David I.; Graham, Brett A. (Frontiers in Molecular Neuroscience, 2020)
Neurons located in dorsal root ganglia (DRG) are crucial for transmitting peripheral sensations such as proprioception, touch, temperature and nociception to the spinal cord before propagating these signals to higher brain structures. To date, difficulty in identifying modality-specific DRG neurons has limited our ability to study specific populations in detail. As the calcium binding protein parvalbumin (PV) is considered one of the best available neurochemical markers for proprioceptive DRG cells we used a transgenic mouse line (PVeGFP), with green fluorescent protein (GFP) expressed under a PV promotor, to study the functional and molecular properties of putative proprioceptive neurons. Immunohistochemistry on sectioned lumbar DRGs showed 100% overlap between GFP positive (GFP+) and PV-containing cells, confirming the PVeGFP mouse accurately labelled PV neurons. Targeted patch-clamp recording from isolated GFP+ and GFP negative (GFP-) neurons showed the passive membrane properties of the two groups were similar, however their active properties differed markedly. All GFP+ neurons fired a single spike in response to sustained current injection and their action potentials had faster rise times, lower thresholds and shorter half widths. A hyperpolarization-activated current (Ih) was observed in all GFP+ neurons but was rarely noted in the GFP- population (100% vs 11%). Additionally, for GFP+ neurons, Ih activation rates varied markedly, indicating potential differences in the underlying hyperpolarization-activated cyclic nucleotide-gated channel (HCN) subunit expression responsible for the current kinetics. Furthermore, qPCR showed the HCN subunits 1, 2, and 4 were more abundant in GFP+ neurons, while HCN 3 was more highly expressed in GFP- neurons. In summary, certain functional properties of GFP+ and GFP- cells differ markedly, providing evidence for a modality specific signaling between the two groups. However, the GFP+ DRG population demonstrates considerable internal heterogeneity when HCN channel properties are considered. We propose this heterogeneity reflects the existence of different peripheral receptors such as tendon organs, muscle spindles or mechanoreceptors in the putative proprioceptive neuron population.